Somewhere in Germany : A Novel - Zweig, Stefanie (Book collections on Project MUSE., 2006)
Follows the Redlichs as they return to Germany in 1947 after 10 years in exile from National Socialism on a Kenyan farm. Walter is so desperate to practice law again that he uproots his complaining wife, Jettel, his clever, nurturing daughter, Regina, and baby Max to Frankfurt, where gentiles either make snide anti-Semitic comments or claim that they saved Jews and used to have many Jewish friends. Zweig has a deft hand with telling anecdotes.